Global convergence of new conjugate gradient method with inexact line search - Chergui Ahmed; Bouali Tahar (International Journal of Electrical and Computer Engineering (IJECE), 2021)
In this paper, We propose a new nonlinear conjugate gradient method (FRA) that satisfies a sufficient descent condition and global convergence under the inexact line search of strong wolf powell. Our numerical experiment shaw the efficiency of the new method in solving a set of problems from the CUTEst package, the proposed new formula gives excellent numerical results at CPU time, number of iterations, number of gradient ratings when compared to WYL, DY, PRP, and FR methods.